Nitrogen migration and transformation characteristics of the soil in karst areas under the combined application of oxalic acid and urea inhibitors - Jiafeng, Wang; Qiuliang, Cai (Frontiers in Plant Science, 2024)
Objective: We investigated the horizontal migration and transformation of nitrogen in soil with oxalic acid and inhibitors (e.g., nitrification inhibitors, DMPP, urease inhibitors, and NBPT) under different soil water contents to provide a basis for the efficient utilization of nitrogen fertilizer in agricultural production in karst areas. Methods: Four nitrogen fertilizers (e.g., ammonium bicarbonate, ammonium sulfate, ammonium chloride, and urea) were applied separately and combined with oxalic acid, DMPP, and NBPT. The ammonium and nitrate nitrogen contents in the different soil layers were measured. The soil columns were cultured through an indoor soil column simulation at water content levels of 30%, 40%, and flooded (50%) for 30 days. Results: Ammonium bicarbonate with inhibitors increased soil NH4 + -N content by 15.42-21.12%. Ammonium sulfate with oxalic acid or NBPT increased soil NH4 + -N content by 27.56-52.25% at 30% and 40% moisture content treatments, compared to ammonium sulfate alone. Urea with DMPP application significantly increased soil NH4 + -N content by 11.93-14.87% at 40% water content and flooded conditions. In all treatments, the NH4 + -N content in the soil treated with 30% water content of ammonium chloride with oxalic acid was the highest. The NH4 + -N content showed a decreasing trend with an increase in the water content. The NO3 --N content in soil treated with ammonium bicarbonate and DMPP was higher than that treated with other nitrogen fertilizers at 30% moisture. The NO3 --N content decreased with increased water content. Under all treatments, ammonium chloride with oxalic acid had the highest percentage of soil NH4 + -N and soil soluble inorganic nitrogen at 30% water content, with 55.29% and 55.97%, respectively. Conclusion: Among the nitrogen fertilizer treatments, the soil NH4 + -N content increased in ammonium bicarbonate with DMPP or NBPT, ammonium sulfate with oxalic acid or NBPT, and urea with DMPP.The four nitrogen fertilizers with DMPP increased the soil NO3 --N content. Nitrogen fertilizer combined with oxalic acid and inhibitors could effectively improve the effective use of nitrogen fertilizer.